Reyes melancólicos en los márgenes de la sociedad y geografía en la literatura medieval - López González, Luis F. (El Colegio de México, 2022)
This article explores the connection between grim melancholy and its psychiatric effects on the monarchical class in the literature of medieval Iberia. Medieval medical epistemology posited that when the black humor burned, the ensuing vapors ascended to the head, creating a disconnect between cognitive perception and the empirical reality. Supported by readings of the works of King Alfonso X, Ramon Llull and Juan Manuel, this study shows how melancholic madness contained within it the impulse to dehumanize the victims of this condition and to expel them from their community and from social life.